The development of a container selection and loading system - Sutad Laotaweesub; Anulark Pinnoi; Pastijn H.; Pisal Yenradee; Partial / Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1996)
A three dimensional container loading problem is discussed in this study. The objective is to find a good loading pattern for each selected container which maximizes volume utilization and minimizes transportation costs for each shipment. Stability of containers, orientation of boxes and strength of boxes will be incorporated in the study. The heuristic algorithm is developed to combine container selection algorithms and container loading algorithms. The container selection algorithm develops a mathematical model for selecting a set of containers and is implemented by C++ programming language. The heuristic container loading algorithm composes of the reference box loading algorithm and the remaining box loading algorithm. The reference box loading algorithm is completed by computer operation to select a reference box for each layer in a container. The remaining box loading algorithm is completed manually to load a remaining box to existing layers in a container. Three examples are used to validate the algorithm and to compare with any existing solution. The algorithm showed that it can be applied to the realistic problem characterized by various sizes and uppermost face constraints of boxes. The algorithms also provided an effective volume utilization for many containers.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Advanced Technologies
Thesis (M. Eng.) - Asian Institute of Technology, 1996
Keywords: Containers; Loading and unloading